Nossos pareceristas: os bastidores da produção científica - Brait, Beth; Pistori, Maria Helena Cruz; Lopes-Dugnani, Bruna; Philippov, Renata (Bakhtiniana. Revista de Estudos do Discurso, 2020)
Editorial 15.4